Asymptotic estimates for the solutions of boundary-value problems with initial jump for linear differential equations with small parameter in the coefficients of derivatives - Kasymov, K. A.; Nurgabyl, D. N.; Uaissov, A. B. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish asymptotic estimates for the solutions of singularly perturbed boundary-value problems with initial jumps.